An empirical formula to assess ultimate strength of initially deflected plate: Part 2 = combined longitudinal compression and lateral pressure - Kim, D.K. (Elsevier Ltd, 2022)
This study proposes an empirical formula to predict the ultimate strength of the initially deflected plate subjected to combined longitudinal compression and lateral pressure. The reliable plate scenarios selected are analysed by the ALPS/ULSAP (= Analysis of Large Plated Structures/Ultimate Limit State Assessment Program) method. In total, 5,600 plate scenarios, including the effects of geometry, material and applied load properties, are generated and used as input data for structural analysis to obtain the ultimate strength of the plates. In particular, five water depths (h) cases (i.e., 0, 5, 10, 15, and 20 m), four material yield strength (i.e., 235, 275, 315, and 355 MPa) and various initial deflection amounts were considered together with the wide range of geometric properties. The empirical formula obtained shows good agreement with ALPS/ULSAP simulation results (R2 = 0.994). The applicability of the outcome verified by statistical analysis and the effect of individual parameters considered on the ultimate strength of the plate is documented. The valuable examples are also provided with a detailed user guide. The obtained result may help estimate the ULS characteristic of the plate under combined compression and lateral pressure. Also, it can be used as a practical design guide for the robust design of the ship's plate. Â© 2022 Elsevier Ltd